Biological oxidation of Mn(II) coupled with nitrification for removal and recovery of minor metals by downflow hanging sponge reactor. (1st January 2015) - Cao, Linh Thi Thuy; Kodera, Hiroya; Abe, Kenichi; Imachi, Hiroyuki; Aoi, Yoshiteru; Kindaichi, Tomonori; Ozaki, Noriatsu; Ohashi, Akiyoshi
Abstract: Biogenic manganese oxides (bio-MnO2 ) have been shown to absorb minor metals. Bioreactor cultivation of heterotrophic manganese oxidizing bacteria (MnOB), which produce bio-MnO2 via oxidation of Mn (II), can be expected to be involved in a promising system for removal and recovery of minor metals from wastewater. However, MnOB enrichment in wastewater treatment is difficult. This study investigated whether MnOB can be cultivated when coupled with nitrification in a system in which soluble microbial products (SMP) from nitrifiers are provided to MnOB as a substrate. A downflow hanging sponge (DHS) reactor was applied for MnOB cultivation with ammonium (NH4 + ) and Mn (II) continuously supplied. During long-term operation, Mn (II) oxidation was successfully established at a rate of 48 g Mn m −3 d −1 and bio-MnO2 that formed on the sponges were recovered from the bottom of the reactor. The results also revealed that Ni and Co added to the influent were simultaneously removed. Microbial 16S rRNA gene clone analysis identified nitrifiers supporting MnOB growth and showed that only one clone of Bacillus subtilis, which was affiliated with a known MnOB cluster, was present, suggesting the existence of other novel bacteria with the ability to oxidize Mn (II). Graphical abstract: Highlights: A downflow hanging sponge reactor was applied to cultivate Mn-oxidizing bacteria with nitrifiers. Biogenic manganese oxides were successfully produced. Nitrifiers supporting growth of Mn-oxidizing bacteria were identified. Simultaneous Ni and Co removal with the production of bio-MnO2 was confirmed.